2018
DOI: 10.1039/c8cp02719f
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric acid in atmospheric new particle formation

Abstract: Nitric acid, an air pollutant with strong acidity and oxidizability, can be found in considerable quantities in the gas and aerosol phase. Understanding the role of nitric acid in atmospheric new particle formation is essential to study the complicated nucleation mechanism. Using density functional theory combined with the Atmospheric Clusters Dynamic Code (ACDC), the role of nitric acid in the formation of new particles has been investigated under different atmospheric conditions (different precursor concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…SFA molecule shows an ability to directly participate in the cluster formation, suggesting that SFA can be a “participator” in facilitating NPF. Contrary to other common acid species as reported in our recent works, ,, such organic acids, e.g., lactic acid and glyoxylic acid, and inorganic acids, e.g., nitric acid, can only be indirectly involved in the growth pathway, acting as a “transporter” (which initially participates and eventually evaporates). Note that, like SFA, another two species with sulfonic group, namely, methanesulfonic acid (MSA) and hydroxymethanesulfonic acid (HMSA), are also identified to directly participate in the cluster formation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…SFA molecule shows an ability to directly participate in the cluster formation, suggesting that SFA can be a “participator” in facilitating NPF. Contrary to other common acid species as reported in our recent works, ,, such organic acids, e.g., lactic acid and glyoxylic acid, and inorganic acids, e.g., nitric acid, can only be indirectly involved in the growth pathway, acting as a “transporter” (which initially participates and eventually evaporates). Note that, like SFA, another two species with sulfonic group, namely, methanesulfonic acid (MSA) and hydroxymethanesulfonic acid (HMSA), are also identified to directly participate in the cluster formation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…3c are too slow to compete in urban new-particle formation, this mechanism may provide an important source of new particles in the relatively clean and cold upper free troposphere, where ammonia can be convected from the continental boundary layer 29 and abundant nitric acid is produced by electrical storms 4 . Theoretical studies have also suggested that nitric acid may serve as a chaperone to facilitate sulfuric-acid–ammonia nucleation 30 . Larger (60–1,000 nm) particles consisting largely of ammonium nitrate, along with more than 1 ppbv of ammonia, have been observed by satellite in the upper troposphere during the Asian monsoon anticyclone 4 , and abundant 3–7-nm particles have been observed in situ in the tropical convective region at low temperature and condensation sink 5 .…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…[ 78 ] The artificial bee colony (ABC) algorithm has recently been employed extensively to study atmospherically relevant clusters. [ 79–84 ] Recently, a new systematic method of configurational sampling based on the Fibonacci sphere has been applied to atmospheric molecular clusters. [ 85,86 ] Once all the low‐energy isomers are identified by one of these configurational sampling methods, [ 87 ] the main parameter of interest to be computed using quantum chemistry is the equilibrium constant of formation under atmospherically relevant conditions dictated by the temperature, pressure, and RH.…”
Section: Particle Formationmentioning
confidence: 99%